Bioanalytical method validation and application to a phase 1, double-blind, randomized pharmacokinetic trial of a standardized Centella asiatica (L.) Urban water extract product in healthy older adults - Wright, Kirsten M.; Bollen, Melissa; David, Jason; Mepham, Bridgette; Alcázar Magaña, Armando; McClure, Christine; Maier, Claudia S.; Quinn, Joseph F.; Soumyanath, Amala (Frontiers in Pharmacology, 2023)
Centella asiatica is an herbaceous plant reputed in Eastern medicine to improve memory. Preclinical studies have shown that Centella asiatica aqueous extract (CAW) improves neuronal health, reduces oxidative stress, and positively impacts learning and cognition. This study aimed to develop and validate bioanalytical methods for detecting known bioactive compounds from Centella asiatica in human biological matrices and apply them to a human pharmacokinetic trial in healthy older adults. High performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) was used for detecting triterpenes and caffeoylquinic acids from Centella asiatica, or their metabolites, in human plasma and urine. Validation parameters including linearity, precision, accuracy, recovery and thermal stability were evaluated. The method was applied to a Phase I, randomized, double-blind, crossover trial of two doses (2g or 4g) of a standardized Centella asiatica water extract product (CAP) in eight healthy older adults. Pharmacokinetic parameters were measured over a 12-hour post administration period and acute safety was assessed. The method satisfied US Food & Drug Administration criteria for linearity and recovery for the analytes of interest in human plasma and urine. The method also satisfied criteria for precision and accuracy and medium and high concentrations. Single administration of 2g and 4g of CAP was well tolerated and safe in healthy older adults. The parent triterpene glycosides, asiaticoside and madecassoside, were not detected in plasma and in minimal amounts in urinary excretion analyses, while the aglycones, asiatic acid and This is a provisional file, not the final typeset article madecassic acid, showed readily detectable pharmacokinetic profiles. Similarly, the di-caffeoylquinic acids and mono-caffeoylquinic acids were detected in low quantities, while their putative metabolites showed readily detectable pharmacokinetic profiles and urinary excretion. This method was able to identify and calculate the concentration of triterpenes and caffeoylquinic acids from Centella asiatica, or their metabolites, in human plasma and urine. The oral absorption of these key compounds from CAP, and its acute safety in healthy older adults, support the use of this Centella asiatica product in future clinical trials.